"Elixir of youth" or "Cancer potion"? The battle for the purse of the middle-aged woman and the role of the media in reporting themes in medical science - Lotter, Rene Louise (Stellenbosch : Stellenbosch University, 2015)
Thesis (MA)--Stellenbosch University, 2004.